Effect of zinc level and the thermal environment on the zootechnical performance and tibia-breaking strength of Japanese quails - Lima, Luiz Arthur dos Anjos; Moraes, Thiago de Assis; Morais, Larissa Kellen da Cunha; de Amorim, Mikael Leal Cabral Menezes; Veríssimo, Tarsys Noan Silva; dos Santos, José Danrley Cavalcante; Maia, Maria Isabelly Leite; dos Santos, Severino Guilherme Caetano Gonçalves; da Costa, Fernando Guilherme Perazzo; Guerra, Ricardo Romão; Carvalho, Lucas Rannier Ribeiro Antonino; Saraiva, Edilson Paes (Frontiers in Veterinary Science, 2025)
Japanese quails (Coturnix coturnix japonica) are sensitive to zinc (Zn) deficiency, a mineral essential for growth, development, and bone health. This study evaluated the effects of different levels of Zn in the diet on zootechnical performance, organ and carcass weight, and tibial breakage resistance in quails from 1 to 42 days of age. A 5 × 2 factorial design was used, consisting of five Zn levels (30, 60, 90, 120, and 150 mg/kg) and two thermal environments (thermal comfort and heat stress), with five replicates of 10 birds per treatment. The results indicate an antagonistic relationship between high levels of Zn in the diet (150 mg/kg) and quail performance, where the addition of the highest Zn level impaired performance. On the other hand, supplementation with the available Zn from the basal diet (30 mg/kg) was sufficient to ensure satisfactory weight gain, better feed conversion, and appropriate carcass and liver weights of quails during the initial rearing phase. At 42 days, supplementation with 150 mg/kg of Zn provided greater resistance to tibial breakage, regardless of thermal conditions. These findings highlight the importance of adjusting Zn supplementation according to the needs of quails at different rearing stages. The study emphasizes the need for a balanced nutritional approach, considering both adequate Zn levels and the management of thermal stress. The combination of appropriate Zn levels in the diet and environmental management, especially concerning thermal stress, is crucial to optimizing productive performance, bone health, and the well-being of the birds. Furthermore, the nutritional Zn requirements for quails in the initial rearing phase may be lower than previously established, without compromising performance. Gradual Zn supplementation, according to the needs of the production stage and environmental conditions, is essential to ensure the health and productivity of the birds.